THE EFFECTIVENESS OF REALITY APPROACH-BASED PSYCHOEDUCATIONAL GROUP WITH SYMBOLIC MODELLING TECHNIQUE TO IMPROVE THE FORGIVENESS OF SMA KESATRIAN 1 STUDENTS - Saputra, Fikie; Yuwono Puji Sugiharto, Dwi; Sutoyo, Anwar (Jurnal Bimbingan Konseling, 2020)
Studies in forgiveness topic have been focused mostly on individual context. Therefore, this study intended to prove that reality approach-based psychoeducational group format with modeling symbolic technique was effective to improve students? forgiveness. The study used repeated measure design with pretest, posttest, and follow up and involved the tenth grade students of SMA Kesatrian 1 Semarang amounted to 273 students. The data of the students were collected using Heartland Forgiveness Scale (HFS). After the intervention, the researchers obtained the mean of students? forgiveness in pretest of (M = 41.33; SD = 01.00), posttest of (M = 61.56 SD = 2.35) and follow-up of (M = 63.11, SD = 2.76). Repeated Measure Test Results proved that symbolic modeling technique was effective to improve students' forgiveness (F (1.8) = 508.76; p <0.001). This study confirmed that the reality approach-based psychoeducational group with symbolic modeling technique effectively improved students? forgivenes.